Students' Mathematical Reasoning Ability in Data Presentation and Processing Material Reviewed from Gender - Heshinta, Linda; Sutama, S; Hidayati, Yulia Maftuhah (Universitas Muhammadiyah Surakarta, 2024)
Purpose: The objectives of this study are twofold. 1) To describe the mathematical reasoning abilities of male students, 2) To describe the mathematical reasoning abilities of students. Methodology: The type and design of the research in this article are qualitative ethnography. The subjects of this study were the principal, teachers, and 23 fifth grade students of Muhammadiyah Elementary School 1 Surakarta. Data collection techniques through interviews, observations, and documentation from test result archives. The data analysis process goes through the stage of data collection from several sources, namely the principal, teachers, students, and supporting documentation. The validity of the data in this study uses triangulation of sources and methods. Results: The results of the research in this article are two. 1) Male students with high category mathematical reasoning ability meet indicators I, 2, and 3, the medium category meet indicators 1 and 3, and the low category only meet indicator 1. 2) Female students with high category mathematical reasoning ability meet all five indicators, the medium category meet indicators 1, 3, 4 and 5, and the low category only meet one indicator, namely the first indicator. Applications/Originality/Value: The findings provide valuable insights for teachers to design differentiated learning strategies that consider gender-specific patterns in mathematical reasoning abilities, supporting more effective development of students’ critical thinking skills